Mental health and psychosocial support programmes for adults in humanitarian emergencies: a systematic review and meta-analysis in low and middle-income countries. Issue 5 (1st October 2019) - Bangpan, Mukdarut; Felix, Lambert; Dickson, Kelly
Abstract : Background: Humanitarian emergencies are a major global health challenge with the potential to have a profound impact on people's mental and psychological health. Effective interventions in humanitarian settings are needed to support the mental health and psychosocial needs of affected populations. To fill this gap, this systematic review synthesises evidence on the effectiveness of a wide range of mental health and psychosocial support (MHPSS) programmes delivered to adults affected by humanitarian emergencies in low and middle-income countries (LMICs). Methods: A comprehensive search of 12 electronic databases, key websites and citation checking was undertaken in 2015 and updated in May 2018. We included controlled trials published in English from 1980. We extracted data and assessed risk of bias prior to performing a meta-analysis using random effects models. When meta-analysis was not used, we narratively described individual trial effect sizes using forest plots. Results: Thirty-five studies were included. Overall, MHPSS programmes show benefits in improved functioning and reducing post-traumatic stress disorder. There are also indications from a limited pool of evidence that cognitive–behavioural therapy and narrative exposure therapy may improve mental health conditions. Other psychotherapy modalities also showed a positive trend in favour of MHPSS programmes for improving several mental health outcomes. Conclusion: In addition to MHPSS programme for improving mental health outcomes in adults affected by humanitarian emergencies in LMICs, there is also a need to generate robust evidence to identify potential impact on broader social dimensions. Doing so could aid the future development of MHPSS programmes and ensure their effective implementation across different humanitarian contexts in LMICs. Future research on MHPSS programmes which focus on basic services and security, community and family programmes, their cost-effectiveness and mechanisms of impact could also strengthen the MHPSS evidence base to better inform policy and practice decision-making in humanitarian settings. Protocol registration number: CRD42016033578.